Pengaruh Kualitas Pelayanan terhadap Kepuasan Konsumen Room Repatriasi di El Hotel Royale Jakarta Kelapa Gading - Afifah, Zahra; Krisnawati, Inti (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2023)
This study aims to determine how much influence the quality of service to customer satisfaction repatriation room at EL Royale Hotel Jakarta. Data collection is done by questionnaire technique. The research method used is quantitative analysis method. The population in this study is a repatriation room visitors, with a sample of 100 respondents. The results showed that from the simple linear regression test results obtained result that the value of the regression coefficient (X) is equal to 0.303 or 30% which gives the meaning that the quality of Service (X) effect on customer satisfaction repatriation room at EL Royale Hotel Kelapa Gading. And the results of the R2 test with a value of 0.086 or 8.6% in this case indicate that the percentage of the effect of the independent variable (quality of service) to the dependent variable (customer satisfaction)is equal to 8.6%. While the remaining 91.4% is influenced or explained by other variables that are not included in this research model.